The Effectiveness Of Giving Ginger And Mint Leaves To The Incidence Of Emesis Gravidarum - Masruroh, Nur; Safitri, Yati Isnaini; Laili, Uliyatul; Ariesta, Ratna; Andriani, Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Hormonal changes in early pregnancy occurs due to rising levels of the hormones estrogen and progesterone. This may result in some of the complaints in mothers in early pregnancy, such as morning sickness or nausea and vomiting. This can be overcome by pharmacological administration of drugs anti-nausea and vomiting as well as non-pharmacological manner mint leaves steeping water also steeping ginger rhizome.The purpose of this study was to analyze effectiveness of given mint leaves and ginger to the incidence of morning sickness in pregnant women. Using a quasi-experimental research design. The population and the sample is first trimester pregnant women who experience morning sickness in Midwives Practice Independently in Surabaya for 3 months. In analysis of respondents given mint leaves using Wilcoxon showed the p-value 0.005 <α of 0.05 means that the mint proven effective in reducing the incidence of morning sickness. In analysis of respondents given ginger result p-value 0.000 <α 0.05, which means that the administration also proved effective steeping ginger reduces the incidence of morning sickness. The results mean rank test showed Award mint leaves steeping steeping ginger 6.87 and 9.86 giving a meaningful that ginger infusion administration more effectively reduce the incidence of morning sickness in comparison with the provision of mint leaves steeping. Pregnant women can reduce morning sickness with non-pharmacological ways to drink the infusion of ginger and mint leaves steeping.